A case report of unusually long episodes of asystole in a severe COVID-19 patient treated with a leadless pacemaker. Issue Volume 4:Issue FI1(2020)Special Issue (30th July 2020) - Cakulev, Ivan; Sahadevan, Jayakumar; Osman, Mohammed Najeeb
Abstract: Background: Experience has been emerging about cardiac manifestations of COVID-19-positive patients. The full cardiac spectrum is still unknown, and management of these patients is challenging. Case summary: We report a COVID-19 patient who developed unusually long asystolic pauses associated with atriventricular block (AV) block and atrial fibrillation who underwent leadless pacemaker implantation. Discussion: Asystole may be a manifestation of COVID-19 infection. A leadless pacemaker is a secure remedy, with limited requirements for follow-up, close interactions, and number of procedures in a COVID-19 patient.